Modelagem matemática para os anos finais do ensino fundamental - PAULA, Jhonata Souza (2024)
This research deals with Mathematical Modeling for the Final Years of Elementary School. It is configured as a qualitative bibliographic, whose general objective was to present a propositional activity of Mathematical Modeling related to the content interpretation of data in graphs and tables. Such content constitutes one of the skills and abilities that students must develop within the scope of the Final Years of Elementary School, as guided by the BNCC (2018). To achieve this, it has the following specific objectives: to situate MM as an active methodology; Know fundamentals of Problem Solving associated with MM; and, to present a proposal for MM and Problem Solving for the 7th year of Elementary School. The theoretical foundation is supported by authors such as: Barbosa (2004), Bertone, Bassanezi and Afelice (2014), Diesel, Baldez and Neumann (2017), Silva (2018) and Scheneiders (2018), Silva Souza (2018), Sodré ( 2019), Silva (2020), Ferreira (2020), Santos and Cunha (2021) and Avelar, Silva and Giordano, (2022). It is believed that the proposed activity can provide mathematical discussion capable of promoting meaningful teaching and learning. Being able to reduce barriers between conceptual knowledge and the practical use of knowledge in reality; There are multiple themes on which to work with MM associated with Problem Solving, but they must have social reality as a starting point.